Griscelli syndrome - Kumar T; Ebenazar Sam; Moses Prabhakar (Wolters Kluwer Medknow Publications, 2006)
Partial albinism with immunodeficiency is a rare and fatal immunologic disorder characterized by pigmentary dilution and variable cellular immunodeficiency. It was initially described in 1978. Primary abnormalities included silvery grayish sheen to the hair, large pigment agglomerations in hair shafts and an abundance of mature melanosomes in melanocytes, with reduced pigmentation of adjacent keratinocytes. We describe a child with Griscelli syndrome who presented with hepatitis, pancytopenia and silvery hair. The diagnosis was confirmed by microscopic skin and hair examination.